Pengembangan Media Model Book Flanel Materi Matematika Mengurutkan Bilangan pada Siswa Kelas II SDN Giripurwo Kecamatan Wonogiri Kabupaten Wonogiri - Maryati, Esti; Suharno, Suharno; Pribadi, Benny Agus (Universitas Mathla'ul Anwar Banten, 2023)
Development of Flannel Book Model Media Mathematical Materials Sequencing Numbers for Grade II Students at SD Negeri Giripurwo Wonogiri District Wonogiri Regency, Thesis, Graduate Program in Elementary Education at the Open University. This study aims to (1) describe the media used at SDN Giripurwo Wonogiri. (2) describe the development of the flannel book model media for mathematical material sequencing numbers and students' creativity at SDN Giripurwo Wonogiri. (3) describe the feasibility of the flannel book model for sequencing mathematics material. numbers and students' creativity at SDN Giripurwo Wonogiri. (4) To find out the effectiveness of the Flannel book model media on mathematical material sequencing numbers and students' creativity at SDN Giripurwo Wonogiri. This type of research is development research which adopts the ADDIE development model. Which includes 5 stages. The analysis stage which includes data collection, the design stage which includes planning and manufacture of the initial flannel book product, the development stage namely prototype preparation, expert validation, the implementation stage namely field trials and the final product form. And product effectiveness testing. The research was stopped at the implementation stage. The research was conducted at Giripurwo Elementary School, Wonogiri District, the research subjects were grade 2 students. Data collection techniques were tests, non-tests and interviews. . The data analysis technique applied in this research and development is the T test and Normality Test.